The eNAMPT/TLR4 inflammatory cascade drives the severity of intra-amniotic inflammation in pregnancy and predicts infant outcomes - Mohamed Ahmed; Nancy G. Casanova; Nahla Zaghloul; Akash Gupta; Marisela Rodriguez; Ian R. Robbins; Carrie L. Kempf; Xiaoguang Sun; Jin H. Song; Vivian Reyes Hernon; Saad Sammani; Sara M. Camp; et al. (Frontiers in Physiology, 2023)
Introduction: Intra-amniotic inflammation (IAI) or chorioamnionitis is a common complication of pregnancy producing significant maternal morbidity/mortality, premature birth and neonatal risk of chronic lung diseases such as bronchopulmonary dysplasia (BPD). We examined eNAMPT (extracellular nicotinamide phosphoribosyltransferase), a critical inflammatory DAMP and TLR4 ligand, as a potential therapeutic target to reduce IAI severity and improve adverse fetal/neonatal outcomes.Methods: Blood/tissue samples were examined in: 1) women with histologically-proven chorioamnionitis, 2) very low birth weight (VLBW) neonates, and 3) a preclinical murine pregnancy model of IAI. Groups of pregnant IAI-exposed mice and pups were treated with an eNAMPT-neutralizing mAb.Results: Human placentas from women with histologically-proven chorioamnionitis exhibited dramatic NAMPT expression compared to placentas without chorioamnionitis. Increased NAMPT expression in whole blood from VLBW neonates (day 5) significantly predicted BPD development. Compared to untreated LPS-challenged murine dams (gestational day 15), pups born to eNAMPT mAb-treated dams (gestational days 15/16) exhibited a > 3-fold improved survival, reduced neonate lung eNAMPT/cytokine levels, and reduced development and severity of BPD and pulmonary hypertension (PH) following postnatal exposure to 100% hyperoxia days 1–14. Genome-wide gene expression studies of maternal uterine and neonatal cardiac tissues corroborated eNAMPT mAb-induced reductions in inflammatory pathway genes.Discussion: The eNAMPT/TLR4 inflammatory pathway is a highly druggable contributor to IAI pathobiology during pregnancy with the eNAMPT-neutralizing mAb a novel therapeutic strategy to decrease premature delivery and improve short- and long-term neonatal outcomes. eNAMPT blood expression is a potential biomarker for early prediction of chronic lung disease among premature neonates.